Unveiling the connection: Emotional intelligence and reflective thinking in students’ PISA problem-solving - Anggraini, Intan; Faiziyah, Nuqthy (Universitas Islam Negeri Raden Intan Lampung, 2024)
Based on an international survey, Indonesian students face challenges in mathematics, ranking 64th out of 65 countries in 2012 and 72nd out of 79 in 2018. This research investigates how reflective thinking and emotional intelligence impact students' ability to solve math-based problems. PISA. Conducted with 40 eighth grade students from SMP Negeri 2 Selogiri, this study uses qualitative descriptive methods, including emotional intelligence questionnaires, reflective thinking tests with PISA questions, and interviews. Participants were divided into high, medium and low emotional intelligence groups. Findings show that students with high emotional intelligence (NHR) excel in all indicators of reflective thinking (response, elaboration, contemplation). Those with moderate emotional intelligence (TMP) meet the cues for reaction and elaboration but struggle with rumination. Students with low emotional intelligence (FTA) only achieve response indicators, having difficulty with elaboration and reflection. The study suggests that higher emotional intelligence improves reflective thinking and problem-solving skills, highlighting the need for targeted improvements in Indonesia's mathematics education system.